2022
DOI: 10.1038/s41467-022-35715-2
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis γ-H2A.X-INTERACTING PROTEIN participates in DNA damage response and safeguards chromatin stability

Abstract: Upon the occurrence of DNA double strand breaks (DSB), the proximal histone variant H2A.X is phosphorylated as γ-H2A.X, a critical signal for consequent DSB signaling and repair pathways. Although γ-H2A.X-triggered DNA damage response (DDR) has been well-characterized in yeast and animals, the corresponding pathways in plant DDR are less well understood. Here, we show that an Arabidopsis protein γ-H2A.X-INTERACTING PROTEIN (XIP) can interact with γ-H2A.X. Its C-terminal dual-BRCT-like domain contributes to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…These data suggested that UV-C does not interfere with the ATM/ATR-dependent meiotic genome stability in Arabidopsis meiocytes. In support of this, dysfunction of either ɤH2A.X-Interacting Protein (XIP) or Suppressor of Gamma Response 1 (SOG1), which mediates DSB response via the RAD51-dependent recombination pathway and acts downstream of ATM/ATR to regulate various DNA damage responses, respectively (Fan et al, 2022; Li et al, 2022; Wei et al, 2021; Yoshiyama et al, 2017), showed normal chromosome integrity at both conditions (Fig. 3J).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…These data suggested that UV-C does not interfere with the ATM/ATR-dependent meiotic genome stability in Arabidopsis meiocytes. In support of this, dysfunction of either ɤH2A.X-Interacting Protein (XIP) or Suppressor of Gamma Response 1 (SOG1), which mediates DSB response via the RAD51-dependent recombination pathway and acts downstream of ATM/ATR to regulate various DNA damage responses, respectively (Fan et al, 2022; Li et al, 2022; Wei et al, 2021; Yoshiyama et al, 2017), showed normal chromosome integrity at both conditions (Fig. 3J).…”
Section: Resultsmentioning
confidence: 72%
“…Arabidopsis ( Arabidopsis thaliana ) ecotype Columbia (Col-0) was used as the wild-type. The qrt (Francis et al, 2006), atm-2 (Kurzbauer et al, 2021), atr (Wang et al, 2021a), rfc1 (Yu et al, 2012), xip-101 (Fan et al, 2022), ku70 (Riha et al, 2002), sog1 (Wang et al, 2022a), tdf1 (Tidy et al, 2022), ams (Tidy et al, 2022), jason (Yi et al, 2023), cenh3-8 (Wang et al, 2023) and uvr8 (Huang et al, 2014) mutants, the fluorescent-tagged line (FTL) I3bc (Francis et al, 2007), pCENH3::RFP-CENH3 (Komaki et al, 2020), pUBQ10::GFP-ABD2-GFP (Dyachok et al, 2014), pMAP65-3::GFP-MAP65-3 (Sofroni et al, 2020) and the pAMS::AMS-GFP (Xiong et al, 2016) reporter lines were used in this study. The pMMD1::GUS-GFP reporter line was newly generated.…”
Section: Methodsmentioning
confidence: 99%
“…The SQ/DWD fragment of BCP3 did not interact with NBS1, which could be explained by the sequence divergence between BCP3 and BCP4 (Figure 6D-F). We used AlphaFold2 (Jumper et al, 2021, Evans et al, 2022 to predict interactions between the fragment of NBS1 containing FHA+tBRCT with shortened SQ/DWD region. AlphaFold2 predicted a high confidence interaction with an alpha helix region upstream of the SQ motifs and involving Leu306 and Cys310 of BCP4 and Ser308 and Arg309 of the second BRCT domain of NBS1 (Figure 6G and Supporting Figure 5).…”
Section: Bcp4 Interacts With Nbs1 Of the Mrn Complexmentioning
confidence: 99%
“…We ran AlphaFold-Multimer v2.2 (Evans et al, 2022) for all protein complex predictions. Of the five models generated, we used only the model ranked_1 for further processing and interpretation.…”
Section: Alphafold Predictionsmentioning
confidence: 99%
“…Soon after the occurrence of DSB thousands of kilobases around the newly formed DSB are labeled by phosphorylated form of H2A.X histone variant (γ-H2AX) that participates in the early signaling of the lesion and recruitment of DNA repair machinery proteins (Rogakou et al ., 1999; Stewart et al ., 2003; Lang et al ., 2012; Fan et al ., 2022). Histone γ-H2AX levels were shown to correlate with DNA damage amounts (Friesner et al ., 2005; Redon et al ., 2009; Lee et al ., 2019), and its dynamics of recruitment and loss are employed to measure DSB repair dynamics (Löbrich et al ., 2010; Lee et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%